A Study on Travelers’ Motivation to Provide Online Reviews - Thakur, Chandan Kumar; Vijay, T. Sai; Chatterjee, Tapas Kumar (Indian Journal of Marketing, 2022)
Information communication technology has changed people’s behavior towards gathering and assimilating information resulting in their dependence on electronic word-of-mouth to fulfill their information needs. With the help of the theory of planned behavior as the conceptual base, the present study aimed at examining the role of antecedent factors – to inform other travelers, show concern, express their enjoyment, subjective norms, and perceived behavioral control on travelers’ attitude. Further, the impact of attitude on their intention to write reviews was also studied. The results suggested a significant impact of informing others, concern for others, expressing enjoyment, and subjective norms on travelers’ attitude towards writing reviews. This attitude triggered travelers’ intent to provide reviews. The original contribution of the study is in identifying the antecedent factors influencing travelers’ attitude and intention towards writing online reviews in the context of an emerging market (India).